2014
DOI: 10.1177/000313481408001134
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Low Transfusion and Angioembolization Rates in the Age of Nonoperative Management of Pediatric Blunt Splenic Injury

Abstract: Nonoperative management of hemodynamically stable blunt splenic injury (BSI) is the gold standard in children. Recent studies from nonpediatric surgery-specialized trauma centers have demonstrated a rise in transfusion and angioembolization associated with decreased splenectomy rates. We investigate the rate of splenectomy and nonsurgical interventions (angioembolization, blood transfusion) for BSI in a pediatric surgery-specialized trauma center. We conducted a retrospective review of children (0 to 18 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…(2) Studies have shown a higher use of angioembolisation at adult trauma centres than paediatric trauma centres in the management of paediatric and adolescent splenic injury. (15)(16)(17) It is unclear if this is due to availability or choice, and whether its use increases splenic salvage in children. (15,16,31) This requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Studies have shown a higher use of angioembolisation at adult trauma centres than paediatric trauma centres in the management of paediatric and adolescent splenic injury. (15)(16)(17) It is unclear if this is due to availability or choice, and whether its use increases splenic salvage in children. (15,16,31) This requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…(15)(16)(17) It is unclear if this is due to availability or choice, and whether its use increases splenic salvage in children. (15,16,31) This requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of splenic artery angioembolization in our series is 11% (8 out of 88 patients) and this is consistent with the literature. 25 Blood transfusion requirement is a surrogate of hemoglobin and low hematocrit levels, which indicate ongoing bleeding. We have demonstrated that while low hemoglobin and hematocrit does not predict the need for operative intervention, it does predict the failure of NOM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that NOM management with low transfusion and low splenic angioembolization rates (0.6%) can lead to high splenic preservation rates with low mortality in dedicated pediatric trauma units. 25 Such results are yet to be duplicated in an adult population. This is a single institutional experience from a busy trauma center.…”
Section: Discussionmentioning
confidence: 99%